"Privacy" in Semantic Networks on Chinese Social Media: The Case of Sina Weibo. (8th October 2013) - Yuan, Elaine J.; Feng, Miao; Danowski, James A.
<x xml:space="preserve">Abstract</x> Unprecedented social and technological developments call into question the meanings and boundaries of privacy in contemporary China. This study examines the discourse of privacy on Sina Weibo, the country's largest social medium, by performing a semantic network analysis of 18, 000 postings containing the word " <inline-graphic xlink:href="ark:/27927/pgg3z7cw6p5" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> (privacy)." The cluster analysis identifies 11 distinct yet organically related concept clusters, each representing a unique dimension of meaning of the complex concept. The interpretation of the findings is situated in the discussion of the rapidly evolving private realm in relation to emerging new contexts of the public realm. Privacy, justified for both its instrumental functions and intrinsic values, both reflects and constitutes new forms of sociality on the sociotechno space of Weibo.